The effects of phenolic compounds on the abundance of olive psyllid, Euphyllura straminea Loginova in commercial and promising olive cultivars - Mahmoud Azimi; Aref Marouf; Seyyed E. Shafiei; Azizollah Abdollahi (BMC Plant Biology)
Abstract The olive psyllid (Euphyllura straminea Loginova) has been reported as a key pest of olive in Iran. Field observations have shown that the infestation rates of various olive cultivars differ among olive psyllid. This study aimed to determine the levels of total phenol and 3,4-dihydroxyphenylethanol (DHPE), as well as the horticultural traits of various olive cultivars, such as Zard, Conservolia, Arbequina, Picual, Cornicabra, Kaissy, Direh, and Koroneiki, and how they correlate with the infestation rates of the olive psyllid. The maximum and minimum numbers of psyllid nymphs were observed in the Arbequina (19.79 ± 2.28) and Direh (2.13 ± 0.38) cultivars, respectively. In contrast, the highest and lowest amounts of DHPE were recorded in the inflorescences of the Direh (11.47 ± 0.54 mg/g) and Arbequina (5.37 ± 0.30 mg/g) cultivars, respectively. Moreover, a rise in the concentration of DHPE in the inflorescences of different olive cultivars is associated with a reduction in the nymph population found within those inflorescences. A negative correlation was observed between the amount of total phenol and the number of nymphs on the inflorescence of olive cultivars. It was concluded that DHPE phenolic compounds might play an effective role in pest attack.